The Links Between Police Officers’ Workplace Bullying, Organizational Bullying Risk Factors, Psychological Capital, and Well-Being - Vrublevskaja, Ina; Bagdžiūnienė, Dalia (Psichologija, 2025)
Workplace bullying is a form of aggressive behavior that employees across various fields, including police officers, may encounter. It serves as a significant source of psychosocial stress. It can lead to long-term negative consequences for an employee’s physical and psychological health and overall well-being. Therefore, investigating the organizational and individual factors contributing to workplace bullying among police officers and its impact on their well-being is highly relevant. This study aimed to examine the relationships between workplace bullying, organizational bullying risk factors, psychological capital, and the well-being of police officers. Method. The cross-sectional study employed an online survey as the data collection method. The questionnaire included demographic questions, the Negative Acts Questionnaire (Notelaers et al., 2018), scales measuring Organizational Bullying Risk Factors (Gamian-Wilk, 2018), Psychological Capital (Lorenz et al., 2016), and the WHO-5 Well-Being Index. The sample included 147 police officers from various Lithuanian counties and police departments, 55.8% of whom were women. The average age of the participants was 38.8 years. Correlation, regression, and mediation analyses were conducted to examine the empirical data. Results. The findings revealed that organizational bullying risk factors negatively predicted bullying among police officers. Both organizational risk factors and psychological capital positively and workplace bullying negatively predicted well-being. Furthermore, workplace bullying mediated the relationship between organizational risk factors and officers’ well-being: risk factors were indirectly related to well-being through a reduction in workplace bullying. Recommendations are provided for reducing workplace bullying among Lithuanian police officers with the objective to enhance their well-being.
Keywords: workplace bullying; organizational bullying risk factors; psychological capital; well-being; police officers